2019
DOI: 10.1136/bmjqs-2019-009383
|View full text |Cite
|
Sign up to set email alerts
|

Management of low back pain in Australian emergency departments

Abstract: BackgroundTo describe the diagnoses of people who present to the emergency department (ED) with low back pain (LBP), the proportion of people with a lumbar spine condition who arrived by ambulance, received imaging, opioids and were admitted to hospital; and to explore factors associated with these four outcomes.MethodsIn this retrospective study, we analysed electronic medical records for all adults presenting with LBP at three Australian EDs from January 2016 to June 2018. Outcomes included discharge diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
130
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(146 citation statements)
references
References 35 publications
14
130
2
Order By: Relevance
“…In our cohort, the proportion of patients admitted to the hospital (3.08%) was comparable to studies performed in North America, 3,12 but very low compared to studies performed in Australia, which have shown proportions up to 34% 11,13,14 (Table 1). Previous studies showing admission rates of less than 3% 3,12 evaluated younger cohorts than studies presenting admission rates over 17%.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our cohort, the proportion of patients admitted to the hospital (3.08%) was comparable to studies performed in North America, 3,12 but very low compared to studies performed in Australia, which have shown proportions up to 34% 11,13,14 (Table 1). Previous studies showing admission rates of less than 3% 3,12 evaluated younger cohorts than studies presenting admission rates over 17%.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies showing admission rates of less than 3% 3,12 evaluated younger cohorts than studies presenting admission rates over 17%. 11,13,14 In our cohort, age was not significantly different comparing patients admitted to the hospital and those not admitted; however, that lack of significance may reflect a type II error, as the number of patients admitted in our cohort (n = 16) was small. In fact, our patients admitted to the hospital (mean age 50.4 years) exhibited an age similar to the mean age of patients in studies with larger admission rates, 11,13,14 and those not admitted (mean age 43.6 years) had similar age to cohorts exhibiting lower admission rates.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In high-income countries, such as the USA and Australia, the epidemiology of LBP is well studied and the data show that a significant proportion of LBP patients being admitted to hospital following presentation to emergency departments. 3,21 For example, the USA study showed that between 1998 and 2007, LBP accounted for a total of 183 151 individuals to be admitted to hospital across the country, of which 118 962 (65%) were admitted after presentation to emergency departments. 3 The study in Australia also indicated that the rate of hospital admission through emergency departments was 17.6%.…”
mentioning
confidence: 99%
“…3 The study in Australia also indicated that the rate of hospital admission through emergency departments was 17.6%. 21 Evidence also demonstrates that the rate of hospital admission for LBP following presentation to emergency departments is increasing over time. 22 Population-based epidemiological studies also estimated that the impact of LBP, including a frequent and a large deal of ambulatory medical care visits and hospitalization will increase with time.…”
mentioning
confidence: 99%